Combined IFN-β and PLT Detection Can Identify Kawasaki Disease Efficiently - Huijuan, Kan; Yaping, Dong; Bo, Wang; Miao, Hou; Guanghui, Qian; Wenhua, Yan (Frontiers in Pediatrics, 2021)
Objective: To evaluate the possibility of IFN-β and PLT as biomarkers for the diagnosis of Kawasaki disease Methods:We selected 44 children who were newly diagnosed with Kawasaki disease as KD group. They were divided into the acute phase of KD (A) and the subacut phase of KD (B). They were also separated into groups with and without CAD (CAD+ and CAD-). Meanwhile, 44 children hospitalized with febrile disease and 44 healthy children were selected as a febrile control group(C) and normal control group(D)，which were attended to Children's Hospital of Soochow University at the same time. We detected the concentration of IFN-β and PLT of peripheral blood serum for all three groups and analyzed the difference; Results: We found that the concentration of IFN-β and PLT were much higher than fever control group and healthy control group both at the acute and subscute phase of KD, especially at subacute phase; the difference between groups with statistically significant, P<0.05. ROC curve showed that the AUC of IFN-β and PLT in the acute phase of KD was 0.71 and 0.81 respectively, the sensitivity and the specificity was 97.22%, 63.64% and 57.89%, 73.86%, respectively. The AUC of IFN-β and PLT were raised into 0.88 and 0.93 at subacute phase of KD, with 97.73%, 68.42%and81.82%, 95.45% for sensitivity and specificity. AUC for IFN-β and PLT combined detection at acute and subacute phase of Kawasaki disease was 0.81 and 0.96, with 97.22%, 55.26%and86.36%, 100% for sensitivity and specificity. The cut-off value of IFN-β and PLT was IFN-β=3.51pg/ml and PLT=303*109 at acute phase of KD, IFN-β=4.21pg/ml and PLT=368*109 at subacute phase from Plot versus criterion values. However, there are no significant difference between the CAD- group and the CAD+ for IFN-β and PLT, both P> 0.5, neither at the acute nor at the subacut phase of KD. Conclusion: IFN-β was a more specificity biomarker for KD diagnosis, especially combined with PLT. Our study provided a clinical evidence for over-activation of STING pathway in Kawasaki disease.